1989
DOI: 10.1111/j.1651-2227.1989.tb11059.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Development of Neonatal Jaundice by Increased Umbilical Cord Blood Bilirubin

Abstract: Umbilical cord serum bilirubin concentration as a predictor of subsequent jaundice was studied in 291 newborns. It was possible to define subgroups of infants with significantly higher or lower risks of developing jaundice. If cord bilirubin was below 20 mumol/l, 2.9% became jaundiced as opposed to 85% if cord bilirubin was above 40 mumol/l. Furthermore, 57% of jaundiced infants with cord bilirubin above 40 mumol/l required phototherapy, but only 9% if cord bilirubin was 40 mumol/l or lower (p less than 0.003)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 12 publications
9
44
2
1
Order By: Relevance
“…18 In contrast studies by Taksande A et al, Rostami et al, Knudsen A, found no association between mode of delivery and significant hyperbilirubinemia. 15,[19][20] This does not match with the inference of this study.…”
Section: Discussioncontrasting
confidence: 58%
“…18 In contrast studies by Taksande A et al, Rostami et al, Knudsen A, found no association between mode of delivery and significant hyperbilirubinemia. 15,[19][20] This does not match with the inference of this study.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, the latter group also presented a higher chance of needing to undergo phototherapy. Knudsen,24 in 1989, carried out a study to demonstrate that jaundiced newborns presented higher umbilical cord blood bilirubin levels than newborns without clinical jaundice. In addition, the number of jaundiced newborns undergoing phototherapy was significantly higher when these levels were higher than 2.3 mg/100 ml, in comparison with the number of jaundiced newborns with no need for treatment and whose bilirubin levels were lower than or equal to 2.3 mg/100 ml.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore assumed a cord TcB level of 1.7 mg per 100 ml based on published values of mean bilirubin levels in the cord blood. [12][13][14] When this was done, gestational age groups, feeding method, the calculated rate of rise and birth weight all entered the model and provided a c-statistic for the ROC curve of 0.903 (not significantly different from our original model P ¼ 0.316). When the last measured TcB was substituted for the peak TcB, the same variables entered the model (gestational age, feeding and percentile groups) with a c-statistic for the ROC curve of 0.873, not significantly different from either of the earlier calculated ROC curves (P ¼ 0.292).…”
Section: Between 1 February 2005 and 28mentioning
confidence: 99%